Morbimortality of newborn care in hospitals of the ecuadorian austro (Horizontes de Enfermería, 2018)
In order to identify the most recurrent pathologies in newborns that cause disease and even death, a study was carried out in three public hospitals in the Ecuadorian Austro, which served to gain insight into the importance of good prenatal care , Preconceived and timely during childbirth. The main objective was to determine and carry out a quantitative study of the pathologies that affect the newborns treated in the hospitals of Canton Cañar, Azogues and Cuenca, besides, it has psychosocial and statistical implications since the neonatal population of our country, Is affected daily and in this way the mortality rate as morbidity increases in the statistical figures all this raising concern in the society in general, being that one of the important points within health is that there must exist zero percent of deaths Both maternal and neonatal. Therefore, it was necessary to intervene to identify these figures through the collection of data in each of the hospital instances; In this way similar percentages were found in these hospitals of the pathologies that affect the health process in a neonate.
Keywords: mortality; morbidity; newly born; attention